Association between the oxidative balance score and testosterone deficiency: a cross-sectional study of the NHANES, 2011–2016 - Jiayi Liu; Chuanyu Ma; Yifu Leng; Jie Qin; Peng Zhang (Scientific Reports)
Abstract There is increasing recognition of the role of oxidative balance in testosterone deficiency (TD). This study investigates the association between the oxidative balance score (OBS) and TD prevalence among adult males in the United States. Data were obtained from a cross-sectional study of 3276 adult men in the 2011–2016 National Health and Nutrition Examination Survey. OBS was assessed based on 16 nutrient and 4 lifestyle components. Multivariate logistic regression and subgroup analyses were conducted to calculate the odds ratios (OR) and 95% confidence intervals (CI) for the association between OBS and TD prevalence. After adjusting for potential confounders, a negative linear association was observed between OBS and TD prevalence (OR = 0.98, 95% CI 0.97–1.00). Participants in the highest OBS tertile had lower odds of TD compared to those in the lowest tertile (OR = 0.92, 95% CI 0.69–1.21). Lifestyle components of OBS were significantly associated with lower TD prevalence (OR = 0.85, 95% CI 0.81–0.90). Furthermore, least absolute shrinkage and selection operator regression identified key OBS components most strongly associated with TD, with physical activity exerting the greatest influence. A predictive nomogram model incorporating these components demonstrated a discriminatory power with an area under the curve of 0.744 (95% CI 72.4–76.4%). In conclusion, this study demonstrates an inverse association between OBS and TD prevalence, suggesting a potential role of oxidative balance in testosterone regulation among US males.